ASPEK HUKUM CLASS ACTION DAN CITIZEN LAW SUIT SERTA PERKEMBANGANNYA DI INDONESIA - Iqbal, Moch (Jurnal Hukum dan Peradilan, 2012)
The assertion aspects and Citizen Law Class Action Law Suit in fact has been recognized and accepted by the Judge and Judicial us, this condition affirmed the issuance of the Supreme Court of Indonesia Regulation Number I of 2002. Legal Breakthrough Central Jakarta District Court that receive and examine claims has increased the belief of justice seekers denganadanya decisions on a lawsuit aqua. However, it must be recognized that in the particular jurisdiction in Indonesia, based on research results Research Center of Law and Justice of the Supreme Court still found many judges who do not understand the legal aspects of handling and class action law suit and the citizen. Characteristics of the class action lawsuits and citizen law suit is necessary shared understanding of both the Judge and the community as a plaintiff; To understand the uniqueness of this lawsuit we all need to do a comparison on other countries that have implemented first lawsuit is like America, Canada etc. Keywords: Aspects of Law, Class Action, Citzen Law Suit